Desain Papan Permainan Tokoh Ibnu Battuta - Alfani, Muhammad Hasanudin; Albar, Deni (Fakultas Desain Universitas Komputer Indonesia, 2023)
Ibn Battuta was a Muslim born in the Moroccan population of the Muslim cities of Ibn Battuta, the city of Tangier. Born and raised in the town of Tangier, Ibn Battuta dreamed of traveling to cities far from where he lived. Until he decided to follow the trail of the dream on an expedition. The exploratory story has been written in the book entitled